THE EFFECTS OF OXYTOCIN MASSAGE AND BREAST CARE ON LACTATION OUTCOMES AMONG POSTPARTUM MOTHERS - Dewi Fajar Wati; Syarini Novita (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
Poor breast milk production is the main reason why mothers do not breastfeed early on, as they feel unable to meet their babies' needs and support adequate weight gain. One effective way to increase breast milk production is by caring for the breasts, maintaining hygiene, and performing oxytocin massage. This study aims to determine the effect of oxytocin massage and breast care on the smooth flow of breast milk in postpartum mothers at the PP Hospital in Jakarta. The research method is descriptive analytical using an experimental design with a two-group pretest-posttest design, in which measurements of the smooth flow of breast milk production are carried out using oxytocin massage and breast care. Data collection was conducted from December 2024 to April 2025 with a total sample size of 60 respondents using primary data and the Shapiro-Wilk test for normality, as well as hypothesis analysis using the Mann-Whitney test. Research results: The Mann-Whitney statistical test yielded a p-value of 0.000 α 0.05. Conclusion: Oxytocin massage and breast care have an effect on breast milk production in postpartum mothers in the Maternity Ward at PP Hospital Jakarta. Recommendation: It is hoped that PP Hospital Jakarta can expand the knowledge of health workers in an effort to increase mothers' understanding of the effect of oxytocin massage and breast care on breast milk production.